Midterm outcomes of high-flexion total knee arthroplasty on Japanese lifestyle - Hiroshi Ohno; Minoru Murata; Satoshi Ozu; Nariyasu Matsuoka; Hiroshi Kawamura; Hirokazu Iida (Acta Orthopaedica et Traumatologica Turcica, 2016)
Objective: To evaluate the clinical outcomes after total knee arthroplasty (TKA) using the Genesis II posterior stabilized prosthesis with a high-flex insert during the mid-term follow-up and to assess its effect on the Japanese lifestyle. Materials and methods: Fifty-three consecutive patients (8 men and 45 women) underwent primary TKA. The mean follow-up time was 76 months (5–9 years). Clinical results were assessed with the Japanese Orthopedic Association osteoarthritis knee rating score (JOA knee score), range of motion, and lifestyle changes. Results: The postoperative JOA knee score improved significantly compared to the preoperative JOA knee score. The mean preoperative flexion range improved from 112° to 123° postoperatively (p < 0.05). Additionally, our findings showed that 39% of patients enjoyed a floor-sitting life preoperatively, but only 30% of patients enjoyed floor-sitting life postoperatively. Conclusion: The postoperative range of knee motion and JOA knee score improved after TKA using the Genesis II posterior stabilized prosthesis with a high-flex insert, but the number of patients who enjoyed floor-sitting life decreased from 39% to 30% because of feelings of fear and discomfort.Level of Evidence: Level IV, Therapeutic study Keywords: Knee, Arthroplasty, High flexion, Genesis II, Japanese lifestyle